Mediating role of empathy in the relationships between personality factors, cultural values and prosocial behavior among undergraduates in Riyadh, Saudi Arabia - Abdullah I, Alsalman Arwa (2021)
The level of prosocial behavior among undergraduates may present new challenges to social psychologists. The results of national and global surveys indicate that the rate of prosocial behavior is lower among university students, although little is known about how certain variables contribute to the level of this behavior, particularly in Saudi Arabia. Moreover, considering the importance of empathy as the mediating role between personality factors, cultural values, and prosocial behavior, this study aims to determine the relationship between personality, cultural values, empathy, and prosocial behavior amongst undergraduates in the Riyadh region of Saudi Arabia. It also examines the role of empathy as a mediator in the relationship between personality factors and prosocial behavior. Furthermore, it seeks to determine the role of cultural values in prosocial behavior through empathy. The current research applied cross-sectional design with correlational analysis. Through a multistage sampling technique, data were collected from 460 university students from King Saud University, Imam Muhammad ibn Saud Islamic University, and Majmaah University. Personality factors (neuroticism, extraversion, conscientiousness, agreeableness, and openness) as independent variables were assessed by the International Personality Item Pool (IPIP) (Goldberg et al., 2006). In addition, cultural values (self-direction, stimulation, hedonism, achievement, power, security, tradition, conformity, benevolence, and universalism) as independent variables were evaluated by Twenty Item Values Inventory (TWIVI) (Sandy et al., 2017). Finally, empathy as a mediator variable was measured by the Toronto Empathy Questionnaire (TEQ) (Spreng et al., 2009), while prosocial behavior as a dependent variable was evaluated by Adult Prosocialness Instrument (API) (Caprara et al., 2005). SPSS was used to analyze descriptive statistics, independent sample t-test, Pearson correlation coefficient, Hierarchical Multiple Regression Modelling, and mediation analysis (Process Macro). This study applied three theories/models: Empathy-Altruism Hypothesis, Five-Factor Model, and Values Theory. The findings showed that there are differences in personality factors, cultural values, empathy, and prosocial behavior according to gender. The findings also indicated a positive relationship between extraversion, conscientiousness, agreeableness, and openness and prosocial behavior. However, neuroticism and prosocial behavior had a negative relationship. Cultural values (self-direction, stimulation, hedonism, achievement, power, security, tradition, conformity, benevolence, and universalism) showed significant correlations with prosocial behavior. The current study found that empathy had a significant relationship with prosocial behavior. Conscientiousness, agreeableness, tradition, benevolence, and universalism made it possible to predict prosocial behavior. Furthermore, this study showed that empathy mediates the relationship between personality factors (agreeableness and conscientiousness) and prosocial behavior, as well as between cultural values (benevolence and universalism) and prosocial behavior. Based on these findings, it can be concluded that prosocial behavior can be affected by gender, personality factors, cultural values, and empathy. Female undergraduates with higher levels of conscientiousness, agreeableness, universalism, hedonism, and empathy showed high levels of prosocial behavior. Meanwhile, male undergraduates with higher levels of neuroticism, extraversion, tradition, stimulation, and power, and decreased empathy, had low levels of prosocial behavior. Furthermore, undergraduates with extraversion, conscientiousness, agreeableness, and openness acted prosocially. Aside from this, neuroticism had a negative impact on prosocial behavior, while undergraduates who achieved high scores in self-direction, stimulation, hedonism, achievement, power, security, tradition, conformity, benevolence, and universalism had high levels of prosocial behavior. Finally, empathetic undergraduates behaved more prosocially. Undergraduates who had personality dominance to conscientiousness, and agreeableness and values (benevolence and universalism), tended to be more empathetic and help others. The study suggests some recommendations for the Ministry of Education, universities, and psychologists to develop the level of prosocial behavior in undergraduates by considering the influence of personality factors, cultural values, and empathy. This study also proposes that universities should obtain information on the personalities of new undergraduates by using a screening test to plan treatment strategies with psychologists for undergraduates who are neurotic. Universities should consider their curricula and teaching by focusing on cultural values that enhance the level of prosocial behavior among undergraduates. This study sheds substantial new light on prosocial behavior among undergraduates in Saudi Arabia.